Scalable COVID-19 Detection Enabled by Lab-on-Chip Biosensors - Tymm, Carly (Cell Mol Bioeng, 2020)
INTRODUCTION: The emergence of a novel coronavirus, SARS-CoV-2, has highlighted the need for rapid, accurate, and point-of-care diagnostic testing. As of now, there is not enough testing capacity in the world to meet the stated testing targets, which are expected to skyrocket globally for broader testing during reopening AIM: This review focuses on the development of lab-on-chip biosensing platforms for diagnosis of COVID-19 infection. RESULTS: We discuss advantages of utilizing lab-on-chip technologies in response to the current global pandemic, including their potential for low-cost, rapid sample-to-answer processing times, and ease of integration into a range of healthcare settings. We then highlight the development of magnetic, colorimetric, plasmonic, electrical, and lateral flow-based lab-on-chip technologies for the detection of SARS-CoV-2, in addition to other viruses. We focus on rapid, point-of-care technologies that can be deployed at scale, as such devices could be promising alternatives to the current gold standard of reverse transcription-polymerase chain reaction (RT-PCR) diagnostic testing. CONCLUSION: This review is intended to provide an overview of the current state-of-the-field and serve as a resource for innovative development of new lab-on-chip assays for COVID-19 detection.